All Days 2016
DOI: 10.2118/179867-ms
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Fluorescence for Real-Time Monitoring of Both Scale and Corrosion Inhibitors: A Game-Changing Technique

Abstract: Inhibitor products have been widely used to reduce both steel corrosion and scale deposition on pipelines, tubings and safety valves in critical offshore sites. Their simultaneous injection with brine has gradually increased the lifetime of production wells with incontestable benefits for the oil and gas industry. However, the large use of such additives has not been followed by the development of any efficient technique of dosage that considers the strict requirements of an offshore platform. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Recent efforts in tracer development for the oil industry have instead focused on exploiting other detection modalities relying on spectroscopic analyses that offer enhanced sensitivity compared with conventional methods. Early investigations into the feasibility of deploying fluorescent tracers have suggested that, despite the presence of oil intrinsic background luminescence, the combination of time-resolved fluorescence and long-lived emission should render such issues obsolete . It is well known that the long-lived luminescence characteristics of lanthanide coordination complexes makes such entities suitable as probes for bioassays; the time-resolved component enabled through the coupling of lanthanides and chromophore ligands eliminates background signal/noise that would otherwise convolute the detection of conventional fluorescent probes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent efforts in tracer development for the oil industry have instead focused on exploiting other detection modalities relying on spectroscopic analyses that offer enhanced sensitivity compared with conventional methods. Early investigations into the feasibility of deploying fluorescent tracers have suggested that, despite the presence of oil intrinsic background luminescence, the combination of time-resolved fluorescence and long-lived emission should render such issues obsolete . It is well known that the long-lived luminescence characteristics of lanthanide coordination complexes makes such entities suitable as probes for bioassays; the time-resolved component enabled through the coupling of lanthanides and chromophore ligands eliminates background signal/noise that would otherwise convolute the detection of conventional fluorescent probes .…”
Section: Introductionmentioning
confidence: 99%
“…Early investigations into the feasibility of deploying fluorescent tracers have suggested that, despite the presence of oil intrinsic background luminescence, the combination of time-resolved fluorescence and long-lived emission should render such issues obsolete. 7 It is well known that the long-lived luminescence characteristics of lanthanide coordination complexes makes such entities suitable as probes for bioassays; the time-resolved component enabled through the coupling of lanthanides and chromophore ligands eliminates background signal/noise that would otherwise convolute the detection of conventional fluorescent probes. 8 Additionally, the potential for ligand modification affords the ability to tailor the overall properties of the combined metal−organic complex to meet different specifications required across various applications.…”
Section: Introductionmentioning
confidence: 99%
“…Elegant analytical approaches exploiting high-performance liquid chromatography (HPLC) separation before either fluorescence or mass spectroscopic analysis have become the method of choice for tracer identification and quantification. However, these analyses generally are not field-portable and require sophisticated instrumentation. To resolve these issues, intricate solutions have been devised through the utilization of delayed luminescent species such as lanthanide-ligand pairs embedded within nanoparticle matrixes or inorganic phosphors with persistent emission which can be detected using fluorescence spectroscopy. In these cases, the issue of background hydrocarbon signal is mitigated by the extended time scale of luminescence originating from lanthanide ions or phosphors in comparison to the short-lived fluorescence of hydrocarbon components in the crude oil. Nonetheless, these materials are expensive, difficult to synthesize in large quantities, and limited by the number of potential barcodes that could be deployed.…”
Section: Introductionmentioning
confidence: 99%